In vitro evaluation of biological properties of high-added value ingredients (date juice and date powder) obtained from date co-products - Clara Muñoz-Bas; Rita Vedor; Daniela Machado; Joana Cristina Barbosa; Ana Maria Gomes; José Angel Pérez-Alvarez; Juana Fernández-Lopez (Applied Food Research)
The commercialization of fresh dates results in a significant amount of waste, with approximately 30 % of dates being discarded due to low-grade classification. To combat food waste, value-added products, such as previously dried and milled date powder and date juice, have been obtained from date co-products using environmentally friendly processes. Fresh dates contain a number of valuable nutritional components, including sugars, dietary fibre, essential vitamins, minerals, and bioactive compounds. This study aimed to assess the chemical composition of date juice and powder, in terms of total soluble solids, total dietary fibre, sugars, proteins, moisture, ash and fats. In addition, the total phenolic compounds content was determined, and in chemico antioxidant, antidiabetic and antihypertensive activities, and prebiotic potential were evaluated. In terms of nutritional values, date juice was found to be rich in water-soluble sugars, while date powder presented high concentrations of total dietary fibre. The nutritional composition strongly influenced the total phenolic compounds content (1.575 ± 0.028 mg GAE/g in date powder vs 0.146 ± 0.004 mg GAE/mL in date juice) and bioactivities (antioxidants, antidiabetic and antihypertensive activities), with date powder showing higher values compared to date juice. Prebiotic potential was observed for both by-products for all the strains tested. In this sense, both date juice and date powder proved to be valuable by-products developed to combat food waste.